2019
DOI: 10.3389/fmicb.2019.00268
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 May Be Involved in the Regulation of Colonic Mucosal Microbiota by Vitamin A

Abstract: Objectives: To investigate the specific role of Toll-like receptor 4 (TLR4) in the regulation of the intestinal mucosa-associated microbiota by vitamin A (VA). Methods: Both TLR4 -/- (knockout, KO) and wild-type (WT) female mice were randomly fed a VA normal (VAN) or VA deficient (VAD) diet for 4 weeks to establish the following four mouse model groups: TLR4 -/- mice fed a VAN diet (KO VAN), TLR4 -/- mice fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 58 publications
2
26
2
2
Order By: Relevance
“…Mucispirillum schaedleri is a known colonizer of the mucus layer in the mammalian GIT [52][53][54], and has been previously detected in chickens [55,56], vampire finches (Geospiza septentrionalis; Michel et al [57]) and turkeys [58]. In chickens, caecal M. schaedleri was significantly positively associated with fat deposition [55].…”
Section: Microbial Function In the Shorebird Microbiomementioning
confidence: 97%
“…Mucispirillum schaedleri is a known colonizer of the mucus layer in the mammalian GIT [52][53][54], and has been previously detected in chickens [55,56], vampire finches (Geospiza septentrionalis; Michel et al [57]) and turkeys [58]. In chickens, caecal M. schaedleri was significantly positively associated with fat deposition [55].…”
Section: Microbial Function In the Shorebird Microbiomementioning
confidence: 97%
“…Vitamin A (VA) is a commonly used food supplement that maintains visual function, tissue development, differentiation, and immune response. Particularly, VA has been confirmed having its critical role of anti‐inflammatory effect (Xiao et al, ; Zhang et al, ). Interestingly, VA plays an essential role in tight junctions in vitro (Osanai, ; Rybakovsky et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…in mice after interventions with prebiotics and probiotics is significantly higher than that in model mice ( P =0.0344) [ 42 ]. Members of the Lachnospiraceae family are involved in maintaining colon health and produce butyric acid to prevent colon cancer in humans [ 43 ]. Studies have found that the relative abundance of intestinal flora Lachnospiraceae_NK4A136_group in rats with advanced cognitive decline is significantly lower than that of normal rats with matched age.…”
Section: Discussionmentioning
confidence: 99%